Sono e fragilidade: um estudo com idosos inseridos em contexto de alta vulnerabilidade social - Mota, Sonia Gonçalves da (Universidade Federal de São Carlos, 2020)
Currently, poor sleep quality and frailty syndrome can be considered important public health problems due to the high prevalence among the elderly and the negative effects on the well-being of affected individuals. Through the early identification of these conditions, interventions can be planned to reduce spending on health services and improve the quality of life for these individuals. Studies have been found in the literature on the association between sleep and frailty; however, they are few in number and demonstrate inconsistency in the results. Most showed that night sleep was associated with frailty. Is it the same when it comes to elderly people living in poverty? The aim of this research was to analyze the relationship between sleep and frailty among elderly people registered in a Family Health Unit in a context of high social vulnerability. This is a descriptive, cross-sectional study, based on the quantitative method of investigation. 81 elderly people were interviewed using the following instruments: Characterization of the elderly, Pittsburgh sleep quality index (PSQI), Frailty criteria proposed by Linda Fried (adapted), Mini Mental State Examination, Geriatric Depression Scale, Katz Index for basic activities of daily living and Lawton's scale of instrumental activities of daily living. Fisher's exact test and Pearson's χ2 test were used. The level of significance was set at 5%. The results showed a predominance of elderly women, aged 60 to 69 years, white, with a partner, Catholics and retirees. Regarding sleep, 50.6% of the elderly had poor quality sleep, 33.3% good quality sleep and 16.1% sleep disorders. As for frailty, 61.7% of the elderly were pre-frail, 33.3% were frail and 5.0% were not frail. Statistically significant results were found between sleep and: level of frailty (p = 0.026) and the criterion “slow gait” (p = 0.000). Approximately 29.6% of frail elderly and 9.3% of robust / pre-frail elderly scored for sleep disorders. Approximately 30.4% of the elderly with slow gait and 10.4% without slowing presented sleep disorders. It was concluded that frail and slow gait elderly people had a higher prevalence of sleep-related complaints when compared to pre-frail and non-frail elderly people and those who did not have slow gait, respectively. These results can sensitize primary health care professionals in order to identify complaints early and implement assertive strategies in order to avoid adverse health outcomes and improve the quality of life of these individuals.
Sleep and frailty: a study with older adults in a high social vulnerability context
Keywords: Idoso Fragilizado; Sono; Vulnerabilidade Social; Saúde da Família; Enfermagem Geriátrica; CIENCIAS DA SAUDE